Evaluating Prisons, Prisoners and Others - Heylin, Greg (Trinity College Dublin, 2001)
Evaluating Prisons, Prisoners and Others advocates evaluation as one powerful means of countering the fatalism engendered by the literature of the failure of prison and Foucault?s analysis of power. It argues that rather than prison itself being the failure, it might be characterised as a container of last resort for those whom society has failed or who have failed in society. Therefore, as well as evaluating aspects of prison and prison programmes it is necessary to evaluate other aspects of the criminal justice systems and social measures aimed at preventing crime. Seven case studies covering a range of programmes and methods are presented. Resistances to evaluation and possible responses to these are also considered.
Keywords: Public Policy; Prisons; Ireland